NUMERICAL MODELS FOR DISSOLVED CONTAMINANT TRANSPORT IN VERTICAL PROFILE OF VADOSE ZONE - FADLIAH RUSYDI , ANNA
Vadose zone is the zone between the land surface and the regional water table. This zone is important because contaminants in this zone are often introduced into the environment and eventually are transported to groundwater. An understanding of how chemicals could migrate through this zone is necessary to prevent groundwater contamination. Dissolved contaminants would reach the groundwater together with water flow. Dissolved contaminants transport in vadose zone could be explained with Richard (1931) and contaminant transport equations. Based on these equations, 1D numerical model could be made. Contaminants transport profile in vadose zone could be explained by this model. The numerical model was made for sandy loam and silty clay loam soil. The model was solved by explicit finite difference scheme using Matlab versi 7.7. The calculation is executed for every time and distance. The results of the model showed that contaminants movement slightly lags behind the water movement. Besides, contaminants transport also retarded by the reactivity of contaminants. Model verification showed that this current numerical model was valid.